Analisis Strategi Pemasaran Tempe Kelompok Usaha Kecil Menengah (UKM) di Desa Sei Mencirim Kecamatan Sunggal Kabupaten Deli Serdang - Mardiana, Siti; Yanis, M. Nazarul; Ayu, Sri Fajar (Universitas Medan Area, 2018)
This research used descriptive and qualitative methods, with 3 samples of tempe entrepreneurs. The analytical tools are marketing channel analysis, marketing margin, marketing efficiency and SWOT. The average age of producer is 35 years with an average education level is 12 years. The results of marketing channel analysis consist of II type, that is channel I from producer to retailer then consumer. Channel II from the manufacturer directly to the consumer and is on the order of highest efficiency. The producer performs all marketing functions except the purchase function. While retailers only perform the functions of purchasing, sales, storage, financing, and market information. Price spread and share margin marketing agency on channel I is the average price of producers per pack starting from Rp 800/100 gram and Rp 1,500/200 gram. Component manufacturer cost Rp 635.9/100 gram and Rp 981,8/200 gram. Production Margin Rp 164,1/100 gram and Rp 518,2/200 gram. Production profit margin ratio of 0.3/100 grams and 0.5/200 grams. The selling price of retailers for consumers is Rp 1,009,7/100 gram and Rp 2,009,7/200 gram. With marketing costs Rp 7.5/pack. Retail profit margin of Rp 202.1/100 gram and Rp 502,1/200 gram. Retail profit margin ratio of 31.5/100 grams and 78.3/200 grams. Components share the producer cost margin of 63%/100 grams and 48.9%/200 grams. It is also known that the largest total cost margin share is issued by retailers 0.7%/100 gram and 0.4%/200 gram. The retail profit margin is 20%/100 gram and 25%/200 gram. On channel II the marketing margin is Rp 0/pack. Average manufacturer price of Rp 800/100 gram and Rp 1,500/200 gram. Costs incurred by producers Rp 635.9/100 gram and Rp 981,8/200 gram. Profit margin ratio is 0.3/100 gram, profit margin ratio is 0.5/200 gram, producer margin share 100%, producer profit margin 16.2% / 100 gram and 25,8% / 200 gram. SWOT analysis of internal-external matrix on tempe industry business is in quadrant I, then marketing strategy applied in this quadrant is SO (Strength-Opportunities).Keywords : Marketing Strategy, Tempe, Sei Mencirim, SWOT